Oxygen‐Doped 2D In2Se3 Nanosheets with Extended In‐Plane Lattice Strain for Highly Efficient Piezoelectric Energy Harvesting - Ji Yeon Kim; Woohyun Hwang; Seo Yeon Han; Ye Seul Jung; Fengyi Pang; Wenhu Shen; Cheolmin Park; Sang‐Woo Kim; Aloysius Soon; Yong Soo Cho (Advanced Science)
Abstract With the emergence of electromechanical devices, considerable efforts have been devoted to improving the piezoelectricity of 2D materials. Herein, an anion‐doping approach is proposed as an effective way to enhance the piezoelectricity of α‐In2Se3 nanosheets, which has a rare asymmetric structure in both the in‐plane and out‐of‐plane directions. As the O2 plasma treatment gradually substitutes selenium with oxygen, it changes the crystal structure, creating a larger lattice distortion and, thus, an extended dipole moment. Prior to the O2 treatment, the lattice extension is deliberately maximized in the lateral direction by imposing in situ tensile strain during the exfoliation process for preparing the nanosheets. Combining doping and strain engineering substantially enhances the piezoelectric coefficient and electromechanical energy conversion. As a result, the optimal harvester with a 0.9% in situ strain and 10 min plasma exposure achieves the highest piezoelectric energy harvesting values of ≈13.5 nA and ≈420 µW cm−2 under bending operation, outperforming all previously reported 2D materials. Theoretical estimation of the structural changes and polarization with gradual oxygen substitution supports the observed dependence of the electromechanical performance.